The concept of a forward scattering micro-sensors radar network for situational awareness - Antoniou, Michail; Sizov, Vladimir; Hu, Cheng; Jancovic, Peter; Raja Abdullah, Raja Syamsul Azmir; Abdul Rashid, Nur Emileen; Cherniakov, Mike (IEEE, 2008)
The concept of a novel forward scattering micro-radar wireless network for ground targets detection and recognition is presented. The system topology and structure are described first, followed by a summary of the system’s capabilities and applications. Signal processing strategies used for target detection, parameter estimation and automatic target recognition are briefly explained and supported with experimental results.